PWE-194 The routine use of transient elastography to detect liver changes in chronic pancreatitis patients. (22nd June 2015) - Yee, A; Chin, S; Adair, RA; Jayne, DG; Smith, AM
Abstract : Introduction: Chronic Pancreatitis (CP) can cause obstruction of the common bile duct. Biliary drainage is often suboptimal due to coexistent CP complications. The effect of protracted biliary obstruction on liver fibrosis has not been assessed in CP patients. The aim of the study is to determine the usefulness of non-invasive transient elastography (TE) - FibroScan© in detecting changes to the liver in CP patients with and without biliary obstruction. Method: 194 CP patients were identified from a prospectively maintained database from 2006 to 2012. 59 patients were scanned, including patients with normal liver function tests (LFTs) and those with abnormal LFTs +/- dilated common bile duct. FibroScan© readings were graded as absent/mild fibrosis (≤ 7.0 kPa), significant fibrosis (7.1–9.4 kPa), severe fibrosis (9.5–12.4 kPa), cirrhosis (≥12.5 kPa). Results: The study group included 44 males and 15 females with CP. Median age was 69 yrs (37–88). The aetiological agent was alcohol in 43%. The median TE was 8.2 (2.5–34.3) kPa with 59.3% normal. Correlation for the whole group was found between pancreas atrophy (p = 0.017, median 7.7 kPa), Cambridge classification III (p = 0.010, median 10.7 kPa) and Creon® >80000 units tds (p = 0.010, median 7.8 kPa). For alcohol aetiology only, this was found with Creon® >80000 units tds (p = 0.018, median 11.2 kPa), abnormal bilirubin (p = 0.005, median 13.6 kPa) and intrahepatic duct dilatation (p = 0.027, median 12.0 kPa). 22% had significant fibrosis, 6.8% had severe fibrosis and 11.9% had values consistent with possible cirrhosis. The rate of fibrosis in this group was determined to be 28.8% with 47% (8/17) having normal serum LFTs. Conclusion: This study suggests that even asymptomatic CP patients with normal liver function tests may have changes of their liver ranging from mild fibrosis to cirrhosis. Routine use of FibroScan© may be useful for the surveillance and detection of early liver disease in CP patients in the outpatient setting so that timely management can be initiated. Disclosure of interest: None Declared. References: Frossard JL, et al . The role of transient elastography in the detection of liver disease in patients with chronic pancreatitis. Liver Int. 2013;33(7):1121–1127 Fraquelli M, et al . Reproducibility of transient elastography in the evaluation of liver fibrosis in patients with chronic liver disease. Gut 2007;56(7):968–973 Braganza JM, et al . Chronic pancreatitis. Lancet 2011;377(9772): 1184–1197 Scobie BA, Summerskill WH. Hepatic Cirrhosis Secondary to Obstruction of the Biliary System. Am J Dig Dis. 1965;10:135–146